Knowledge Visualization Currents From Text to Art to Culture - Marchese, Francis T.; Banissi, Ebad.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2013)
Lying at the intersection of education, art, and cultural heritage, visualization is a powerful tool for representing and interpreting complex information. This unique text/reference reviews the evolution of the field of visualization, providing innovative examples of applied knowledge visualization from disciplines as varied as law, business management, the arts and humanities. With coverage of theoretical and practical aspects of visualization from ancient Sumerian tablets through to twenty-first century legal contracts, this work underscores the important role that the process of visualization plays in extracting, organizing, and crystallizing the concepts found in complex data. Topics and features: Contains contributions from an international selection of preeminent authorities Presents a thorough introduction to the discipline of knowledge visualization, its current state of affairs and possible future developments Examines how tables have been used for information visualization in historical textual documents Discusses the application of visualization techniques for knowledge transfer in business relationships, and for the linguistic exploration and analysis of sensory descriptions Investigates the use of visualization to understand orchestral music scores, the optical theory behind Renaissance art, and to assist in the reconstruction of an historic church Describes immersive 360 degree stereographic visualization, knowledge-embedded embodied interaction, and a novel methodology for the analysis of architectural forms This interdisciplinary collection of the state of the art in knowledge visualization will be of considerable interest to researchers from a broad spectrum of backgrounds in both industry and academia.
Part I: Knowledge Visualization Background -- What is an Effective Knowledge Visualization? -- What Is Knowledge Visualization? -- Part II: Text -- Tables and Early Information Visualization -- Contract Clarity and Usability through Visualization -- From Culture to Text to Interactive Visualization of Wine Reviews -- Part III: Art -- Colorscore: Visualization and Condensation of Structure of Classical Music -- The Implications of David Hockney$1 (Bs Thesis for 3D Computer Graphics -- Practice of Using Virtual Reconstruction in the Restoration of Monumental Painting -- Part IV: Culture -- Mediation of Knowledge Construction of Historic Sites -- Memory, Difference, and Information -- Cultural Data Sculpting.s
Keywords: Computer science; Data mining; Computer graphics; Visualization; Computer Science; Computer Graphics; Data Mining and Knowledge Discovery; Visualization; User Interfaces and Human Computer Interaction